2022
DOI: 10.1093/humrep/deac236
|View full text |Cite
|
Sign up to set email alerts
|

Expectant management versus IUI in unexplained subfertility and a poor pregnancy prognosis (EXIUI study): a randomized controlled trial

Abstract: STUDY QUESTION For couples with unexplained subfertility and a poor prognosis for natural conception, is 6 months expectant management (EM) inferior to IUI with ovarian stimulation (IUI-OS), in terms of live births? SUMMARY ANSWER In couples with unexplained subfertility and a poor prognosis for natural conception, 6 months of EM is inferior compared to IUI-OS in terms of live births. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Two typical examples of RCTs with such a design that stopped prematurely were a trial that compared intrauterine insemination (IUI) with expectant management in couples with unexplained subfertility, and a trial that compared immediate delivery with temporizing management in women between 27+5 and 33+5 weeks of gestation admitted for early-onset severe preeclampsia with or without HELLP syndrome (33,81).…”
Section: Discussionmentioning
confidence: 99%
“…Two typical examples of RCTs with such a design that stopped prematurely were a trial that compared intrauterine insemination (IUI) with expectant management in couples with unexplained subfertility, and a trial that compared immediate delivery with temporizing management in women between 27+5 and 33+5 weeks of gestation admitted for early-onset severe preeclampsia with or without HELLP syndrome (33,81).…”
Section: Discussionmentioning
confidence: 99%
“… Steures et al (2006) randomized 253 couples with an intermediate prognosis for natural conception (30–40% in 12 months) and found that IUI with hyperstimulation did not increase ongoing pregnancy rates after 6 months. In contrast, two other RCTs, the TUI (The Uterine Insemination) and the EXIUI (Expectant management vs IUI in unexplained subfertility and a poor pregnancy prognosis) trials, were carried out in couples with a poor prognosis for natural conception (<30% in 12 months) ( Farquhar et al , 2018 ; Wessel et al , 2022 ). These trials, both with a large sample size, clearly demonstrated that IUI with ovarian stimulation is more effective than expectant management in these women.…”
Section: Prognosis and Unexplained Infertilitymentioning
confidence: 99%
“…Thus, the prognostic index for natural conception, as established with the Hunault model, can be used as a treatment selection marker in couples with unexplained infertility ( Hunault et al , 2004 ). In couples with a good prognosis, IUI with ovarian stimulation does not benefit over expectant management, while in poor prognosis couples, IUI with hyperstimulation should be recommended, with cancellation policies in the presence of multiple follicular development to reduce the risk of multiple pregnancy ( Wang et al , 2019b ; Wessel et al , 2022 ).…”
Section: Prognosis and Unexplained Infertilitymentioning
confidence: 99%